Waves of reform – analysing a history of educational development concepts - Gedda, Oskar; Wikberg-Nilsson, Åsa; Garvare, Rickard; Edström, Kristina (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2016)
Luleå University of Technology (LTU) joined the CDIO Initiative in 2015, and a pilot projectinvolving four engineering programs is now well underway. Studying this case, it strikes us asinteresting that this happens now, as LTU could obviously have joined CDIO at least adecade earlier. In order to understand the internal processes leading to this outcome, westudied documents and consulted with key persons. In this paper, the history of reformapproaches at LTU is described and analysed. We focus in particular on the Arena concept,which appears to have kept LTU from joining CDIO, and the Pedagogical Idea, which iscompatible with CDIO and eventually led to the adoption. Reflecting critically on the lessonslearned from the LTU case, and drawing on theory and literature, we consider what cansupport or hinder the adoption of an educational reform concept in the organisation. Somefactors concern the nature of the reform and the strategies of implementation. Further, whatother universities do can be an influence. Godkänd; 2016; 20160616 (asawi)